Adaptive evolution of antioxidase-related genes in hypoxia-tolerant mammals - Wang, Qiu-Ping; Luo, Chao-Yang; Xu, Xiong-Hui; Hu, Wen-Xian; Gai, Yu-Lin; Gong, You-Jing; Mu, Yuan (Frontiers in Genetics, 2024)
To cope with the damage from oxidative stress caused by hypoxia, mammals have evolved a series of physiological and biochemical traits, including antioxidant ability. Even many researches about mechanisms of hypoxia evolution have been reported, the limitation about the molecular mechanisms of antioxidase-related genes in mammals living in different environments also has been existed. In this study, we constructed a dataset comprising seven antioxidase-related genes (CAT, SOD1, SOD2, SOD3, GPX1, GPX2, and GPX3) from 43 mammalian species to implement evolutionary analysis. The results showed that six genes (CAT, SOD1, SOD2, SOD3, GPX1, and GPX3) have underwent divergent evolution based on the free ratio (M1) model. Furthermore, multi-ratio model analyses uncovered the divergent evolution between hypoxic and non-hypoxic lineages, as well as various hypoxic lineages. In addition, the branch-site model has identified nine positively selected branches in six genes (CAT, SOD1, SOD2, SOD3, GPX2, and GPX3) that contained 35 positively selected sites, among which 31 positively selected sites were identified in hypoxia-tolerant branches, accounting for 89% of the total number of positively selected sites. Interestingly, 65 parallel/convergent sites were identified in the seven genes. In summary, antioxidase-related genes are subjected to different selective pressures among hypoxia-tolerant species lived in different habitats. This study provides valuable insight into the molecular evolution of antioxidase-related genes in hypoxia evolution in mammals.